Rett Syndrome: A Case Report - Pathak, MR; Neopane, A (Journal of Nepal Paediatric Society, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Rett Syndrome (RS) is a neurodevelopmental disorder in which girls are predominantly affected, transmitted as an X linked dominant inheritance and caused by mutation in MECP2 gene. The basic presentation in RS is regression of previously acquired developmental milestones, lack of social interaction skills and acquired microcephaly after a certain age, which starts in early months of infancy. It is frequently misdiagnosed as autism, cerebral palsy or nonspecific developmental delay and is relatively frequent cause of delayed development in girls. Diagnosis is mainly clinical after excluding the neurodegenerative and other causes of delayed milestones. The chromosomal analysis, confirmatory tool for diagnosis is available in limited centers. The treatment is mainly speech therapy and counseling though few pharmacological agents have been tried with little response. A ten years age girl presented with the history of seizures, regression of speech and delayed motor milestones in our out patient clinic which was subsequently diagnosed as Rett Syndrome. Key Words: Rett syndrome, Developmental Regression, X Linked Dominant. DOI = 10.3126/jnps.v28i1.1402 J. Nepal Paediatr. Soc. Vol.28(1) p.20-22